Improved charge pump for capacitor discharge applications - Toudeshki, Arash Mohammadi (2013)
High-voltage dc has a wide area of application in military, science and industry. Based on the energy equation, in order to produce more potential energy, due to limitations in increasing the capacitance, another parameter which is the voltage must be increased to a higher value. In the recent century, many types of high{voltage generators and voltage multipliers are introduced to do this task, and until now; their development and improvement are subject to be continued. Indeed, a charge pump is another type of voltage multiplier that can produce a dc voltage at its output. Unlike the voltage multipliers that employ to generate a low or high{voltage dc, charge pumps are generally used in low{voltage applications. In this thesis, a novel charge pump is developed for high{voltage applications. By re{designing a voltage multiplier circuit, it attempts to propose a novel charge pump configuration that can produce higher output dc voltage and stored potential energy. Since,the proposed circuit includes many energy storage components, understanding its performance and calculating the output voltage in time{domain seems to be very complicated and time{consuming process. Thus, a circuit theory is used to explain the performance of the circuit in a simple way. Furthermore, this theory offers an equation to explain the correlations between the output voltage and stored potential energy with the input voltage and number of stages. In order to evaluate the proposed circuit, simulation has been carried out, and its output results were compared with calculations. In order to identify a more precise behaviour of the output voltage parameters, in steady{state, and their dependence to the input voltage, number of stages and pumping frequency; an approximate mathematical model optimized for each parameter that can give an enhanced view of the circuit for better understanding of its behaviour. In addition, a new time{domain equation is suggested for the proposed charge pump. Moreover, based on the suggested time{domain equation, a suitable transfer function for both the transient and the steady{state response of the proposed charge pump is calculated. This transfer function can be used for modelling and simulating the circuit as a control system. Ultimately, a prototype circuit of the proposed charge pump with the ability of converting to the conventional circuit with the same values, and circuit parameters have been designed,optimized and fabricated; its output results were compared with the output results of the conventional circuit; and results of calculation and simulation. In this research, the novel charge pump is successfully designed, fabricated and validated. The results show its promised application in science and military.